The onset of active gill respiration in post-embryonic zebrafish (Danio rerio) larvae triggers an increased sensitivity to neurotoxic compounds - Kämmer, Nadine; Erdinger, Lothar; Braunbeck, Thomas (Aquatic toxicology, 2022)
Originally designed as a general alternative to acute fish toxicity testing (AFT), the fish embryo toxicity test (FET) has become subject to concerns with respect to neurotoxic substances. Whereas oxygen uptake in the fish embryo primarily occurs via diffusion across the skin, juvenile and adult fish rely on active ventilation of the gills. As a consequence, substances including, e.g., neurotoxicants which prevent appropriate ventilation of gills (“respiratory failure syndrome”) might lead to suffocation in juvenile and adult fish, but not in skin-breathing embryos. To investigate if this respiratory failure syndrome might play a role for the higher sensitivity of juvenile and adult fish to neurotoxicants, a modified acute toxicity test using post-embryonic, early gill-breathing life-stages of zebrafish was developed with chlorpyrifos, permethrin, lindane, aldicarb, ziram and aniline as test substances. Additionally, a comparative study into bioaccumulation of lipophilic substances with logKow > 3.5 and swimbladder deflation as potential side effects of the respiratory failure syndrome was performed with 4 d old skin-breathing and 12 d old gill-breathing zebrafish. With respect to acute toxicity, post-embryonic 12 d larvae proved to be more sensitive than both embryos (FET) and adult zebrafish (AFT) to all test substances except for permethrin. Accumulation of chlorpyrifos, lindane and permethrin was 1.3- to 5-fold higher in 4 d old than in 12 d old zebrafish, suggesting that (intermediate) storage of substances in the yolk might reduce bioavailability and prevent metabolization, which could be a further reason for lower toxicity in 4 d than in 12 d old zebrafish. Whereas ziram and aniline showed no significant effect on the swimbladder, zebrafish exposed to chlorpyrifos, lindane and permethrin showed significantly deflated swimbladders in 12 d old larvae; in the case of aldicarb, there was a significant hyperinflation in 4 d old larvae. Swimbladder deflation in post-embryonic 12 d zebrafish larvae might be hypothesized as a reason for a lack of internal oxygen supplies during the respiratory failure syndrome, whereas in 4 d old embryos cholinergic hyperinflation of the swimbladder dominates over other effects. Regarding acute lethality, the study provides further evidence that the switch from transcutaneous to branchial respiration in post-embryonic zebrafish life-stages might be the reason for the higher sensitivity of juvenile and adult fish to neurotoxic substances.
Im Text ist "Danio rerio" kursiv geschrieben
Gesehen am 28.08.2022